2012
DOI: 10.1161/circep.111.967992
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Behavior of High Dominant Frequency During Paroxysmal and Persistent Atrial Fibrillation in the Human Left Atrium

Abstract: Background-Sites of high dominant frequency (DF peak ) are thought to indicate the location of drivers of atrial fibrillation (AF), but characterization of their spatiotemporal distribution and stability, critical to their relevance as targets for catheter ablation, requires simultaneous global mapping of the left atrium. Methods and Results-Noncontact electrograms recorded simultaneously from 256 left atrial sites during spontaneous AF were analyzed. After subtraction of the ventricular component, fast Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 33 publications
8
82
0
Order By: Relevance
“…Previous studies showed imperfect correlations between the NCM and contact mapping for 62 random locations in the left atrium [41]. It was also shown that correlation decreased with increasing distance between the endocardial node and the balloon [40,42].…”
Section: Estimating Df Using Ncmmentioning
confidence: 94%
“…Previous studies showed imperfect correlations between the NCM and contact mapping for 62 random locations in the left atrium [41]. It was also shown that correlation decreased with increasing distance between the endocardial node and the balloon [40,42].…”
Section: Estimating Df Using Ncmmentioning
confidence: 94%
“…Ablation based on DF has generally not proved effective. [16][17][18] However, not all AF is the same, and a strong correlation between DF and PS location for stationary rotors may exist. 19 …”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…The inability to combine low-and high-resolution mapping in the intact human heart may also explain why measures of organization and spatial gradients in AF, such as dominant frequency, organizational index, and Shannon entropy, have proven unstable and of no significant clinical utility. 12,13 That the hierarchical nature of AF organization is only revealed at the most global level using complex algorithms may be considered to obviate the need to understand causation at the cell and tissue level. But this would once again make us slaves to the empirical-like when pulmonary vein encirclement only, with or without the aim of isolation was uniformly applied for all clinical presentations of AF, 14 or when variably defined attractive electrograms 15 were indiscriminately ablated as the empirical adjunct.…”
Section: Barriers To Progressmentioning
confidence: 99%